Detrital zircon U–Pb geochronology and provenance of the Neoproterozoic Lower Roan Group, Chambishi Basin, North‐eastern Zambia: Implication for rift evolution of the Congo Craton. (6th March 2019) - Liu, Chun‐Fa; Zhang, Jing; Tang, Li; Yang, Fan; Guo, Jiang‐Tao; Zhou, Cong; Cai, Zhen‐Wang; Bian, Xiao‐Long
Abstract : Zambia Copperbelt hosts numerous world‐class, high‐grade sediment‐hosted stratiform Cu deposits. The Lower Roan Group of the Katanga Supergroup is the main ore host and mainly comprises clastic rocks. In this study, we conducted laser ablation inductively coupled plasma mass spectrometry detrital zircon dating on the sedimentary rocks of the Lower Roan Group in the Chambishi Basin, in order to investigate the Neoproterozoic rift evolution of the Congo Craton. Our results reveal that the main zircon age population (97.1%) falls within 2.1–1.7 Ga (peaks at 1.95 and 1.88 Ga), and minor age populations fall into the Archaean (2.7–2.4 Ga), Palaeoproterozoic (2.3–2.1 Ga), and Mesoproterozoic (1.5–1.05 Ga). Detrital zircons from the Lower Roan Group have distinct oscillatory zoning in cathodoluminescence images, high Th/U ratios (mostly 0.5–2.0), and are sub‐angular, suggesting close detrital provenance. Provenance of the Lower Roan group may have been mainly the Lufubu Metamorphic Complex, Bangweulu Block, and Muva Supergroup, and minor the nearby granitoids of the Irumide Belt. The south‐eastern Congo Craton likely underwent two Neoproterozoic rifting events: the first rift cycle lasted from 880 to 820 Ma when the Lower Roan and Upper Roan groups were deposited in the Roan Basin. After an uplift, the Mwashia, Nguba, and Kundelungu groups of the Katanga Supergroup were likely deposited during the second rift basin development (765–635 Ma). The similar detrital zircon age spectra suggested that the Mwashia Group may have derived from the Lower Roan Group.